Fokus på fiktionen stoppar mordet på Mozart! - Torell, Örjan (Tidskrift för litteraturvetenskap, 2010)
How to Stop the Constant Killing of Mozart by Focusing Fictionality This text is a slightly expanded version of a conference speech, delivered at the University of Umeå 2010-10-14. My purpose is to point out the didactic potential of Aristotle’s mimesis theory, and in particular the idea that the human ability to create fictional worlds constitutes a special way of understanding reality (or rather the notions of reality that we are provided with by our senses and rational thinking). This idea is seen as a prerequisite of the exceptionally dialogic character of Russian literary theory from Potebnya to Bakhtin, and in order to show what that dialogic attitude really means, the contrary formalistic position of Boris Shklovsky – and especially his inability to understand the Aristotelian standpoint of Potebnya – is discussed in some detail. Proposing literary transfer as a modern key to dialogic reading, I try to illustrate what it might contribute even to a super reading of Homer like the one Erich Auerbach carries through in his Mimesis. Finally, I point out, with examples from French scholar Jean-Marie Schaeffer, how make-believe-theory can help to restore the reader as a human being and the literary text as a work of art – and thereby to stop the still on-going killing of Mozart that the Russian formalists, according to Bakhtin (in his – or Mevedev’s? – »Scholarly Salierism«) committed themselves to so long ago.